Constructing an Authoritative Source of Truth in a Changing Information Landscape. Issue 1 (12th April 2022) - Smith, Tyler; Payne, Charles; Shackleton, John
ABSTRACT: In support of the US Army Mission System Architecture Demonstration, Adventium Labs conducted a series of interviews and demonstrations to determine requirements, best practices, and available tool capabilities for building and maintaining an Authoritative Source of Truth (ASoT). An ASoT is a capability that gives definitive answers to queries about a target collection of systems. An ASoT should make information discoverable, enable controlled information sharing, and maintain traceability across time and organizations. The challenges to establishing an ASoT include limited standards adoption by tool vendors, entrenched workflows, and data rights management needs. The systems engineering community can overcome these challenges by keeping ASoT needs at the forefront when planning engineering activities, investing in open and flexible standards for information sharing, and leveraging emerging connectivity tools and model‐based systems engineering methods.